2019
DOI: 10.18542/ragros.v11i1.5248
|View full text |Cite
|
Sign up to set email alerts
|

Frota Pesqueira Comercial Na Amazônia Central: Composição, Origem, Espécies Exploradas E Mercado

Abstract: A pesca no Estado do Amazonas e exercida por pescadores que utilizam embarcados de diferentes categorias, empregando diversificados aparelhos de pesca para explorar uma grande diversidade íctia comercializadas em mercados de pequenos a grandes centros urbanos. Este trabalho apresenta a composição e origem da frota pesqueira no estado do Amazonas atuando entre os anos de 2002 e 2010, seus principais aparelhos de pesca empregados, espécies exploradas e mercados onde a produção é comercializada. As informações an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
6
0
5
Order By: Relevance
“…The preference of riverine communities for consumption of species of this order has already been observed in other studies (Garcez et al, 2009;Silva et al, 2017;Begossi et al, 2019). Characiformes are also the most exploited species by commercial fishing and the most consumed in regional urban centers such as Manaus (Freitas and Rivas, 2006;Corrêa et al, 2014;Faria Junior and Batista, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…The preference of riverine communities for consumption of species of this order has already been observed in other studies (Garcez et al, 2009;Silva et al, 2017;Begossi et al, 2019). Characiformes are also the most exploited species by commercial fishing and the most consumed in regional urban centers such as Manaus (Freitas and Rivas, 2006;Corrêa et al, 2014;Faria Junior and Batista, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…Other studies also indicated the variability of landings according to river regime (Isaac et al, 2015;Sousa et al 2017;Lopes and Freitas, 2018). The peacock bass is among the main species landed, not only in the present study area (Faria Junior and Batista, 2019), but also in other regions (Silva et al, 2017) and in reservoirs where it was introduced (Agostinho et al 2007;Novaes et al, 2015).…”
Section: Discussionmentioning
confidence: 56%
“…The greater number of fishing sites and the greater radius of action of the fishing fleet observed in the lower Amazon River in both hydrological periods is probably related to the size of the cities that were analyzed, the characteristics of the vessels used and a higher level of exploitation of the species in the environments near each urban center (Tregidgo et al, 2017;Faria Junior and Batista, 2019;IBGE, 2021). Parintins, in the lower Amazon River, is the municipality with the largest population (116,439) in relation to Tabatinga (68,502 people) and Benjamin Constant (44,873) in the upper Solimões River and Iranduba (49,718) in the lower Solimões River, and demanded a greater landing (IBGE, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Parintins, in the lower Amazon River, is the municipality with the largest population (116,439) in relation to Tabatinga (68,502 people) and Benjamin Constant (44,873) in the upper Solimões River and Iranduba (49,718) in the lower Solimões River, and demanded a greater landing (IBGE, 2021). In addition, the municipality of Parintins has the second largest number of fishing boats, which have greater storage and transport capacity than other vessels, and which consequently allow fishers to travel greater distances (Faria Junior and Batista, 2019). Keppeler et al (2018), when evaluating indicators of Amazonian fish communities, identified that the distance from the lake to the urban center was positively related to the average size of fish and the dominance of large fish, thus indicating direct human effects caused by fishing or indirect effects by habitat alteration.…”
Section: Discussionmentioning
confidence: 99%